MEMOTRET PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN DIGITAL COMMUNICATION TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - I Putu Gede Aryatna; Melisa Monica; Nopriadi Saputra (Universitas Muhammadiyah Jakarta, 2023)
This study aims to determine: the effect of Perceived Organizational Support on Organizational Citizenship Behavior, the influence of Digital Communication on Organizational Citizenship Behavior, the influence of Perceived Organizational Support and Digital Communication on Organizational Citizenship Behavior. This research was conducted on employees of PT. Tiga Saudara Priantama. This study uses multiple regression analysis to test the hypothesis with a sample of employees. Samples were taken as many as 400 respondents. The results show that there is a partial effect of Perceived Organizational support (X1) on employees' Organizational Citizenship Behavior (OCB) (Y), there is a partial influence and digital communication (X2) on employees' Organizational Citizenship Behavior (OCB) (Y). Perceived Organizational support (X1) and digital communication (X2) simultaneously on the Organizational Citizenship Behavior (OCB) (Y) of employees. This research is limited to Perceived Organizational Support (POS), Digital Communication and Organizational Citizenship Behavior (OCB) variables at PT. Tiga Saudara Priantama during the pandemic which forced employees to work with additional protocols in working in accordance with government recommendations. This study shows how employers can use this research in consideration of improving Organizational Citizenship Behavior (OCB) by implementing Perceived Organizational Support (POS) and improving their employees' Digital Communication.